Cela — ein Entwicklungszentrum im Hochland von Angola - Borchert, Günter (ERDKUNDE, 1961)
Of all European countries Portugal suffers proportionately the greatest population loss through emigration. By means of large scale development schemes, financed by the state, an attempt is made to direct this emigration partly into Portugal’s overseas provinces, especially to Angola. At Cela (350 Km. south-east of Luanda at an altitude of 1,300 m. within the zone of the marginal range) in an agricultural development area, 298 holdings for settlers have so far been created to that end. In this paper an outline is given of its physical background, and organisation, structure and further planning of the settlement association are shown. One of its features is that the employment of native labour is not permitted either in the small holdings (of about 20 ha) or in the large family farms (approximately 100 ha). Cela is an example of a succesful settlement of white farmers in a tropical seasonally humid highland. This project carried out with substantial means and directed by foremost experts also provides a good case for studying general and specific problems of opening up of virgin land and development assistance.